The Argument For: Retaining Income as One of Two Factors in Maine’s School Aid Funding Formula - Brennan, Michael; Delogu, Orlando (Maine Policy Review, 2000)
Brennan and Delogu’s commentary asserts the importance of retaining local household income as a factor in determining school funding formulas in Maine. They note that inclusion of income in school aid equalization formulas has been embraced in over a dozen other states.